Strengthening Legal Protection Against Below Minimum Wages Based on the Principle of Morality - Sulaiman Amiruddin; Bambang Soesatyo (al-Battar: Jurnal Pamungkas Hukum, 2025)
This study examines legal protection for workers receiving wages below the minimum wage in Indonesia by analyzing Government Regulation Number 51 of 2023 on Wages and Law Number 6 of 2023 concerning Job Creation. Employing a normative legal research method with a statutory and conceptual approach, this research evaluates wage regulation and enforcement through Lon L. Fuller’s principle of legal morality, particularly focusing on legal clarity, consistency, certainty, and conformity between regulation and implementation. The findings indicate that although the existing legal framework formally guarantees workers’ rights to decent wages and provides sanctions for violations, its effectiveness remains limited due to weak labor supervision, inconsistent enforcement, regulatory ambiguities, and low employer compliance. From the perspective of legal morality, these deficiencies undermine the moral integrity of wage law, as regulations often fail to function effectively in practice. Therefore, this study argues that strengthening legal protection requires comprehensive policy reform, stricter and more consistent sanctions, optimization of labor inspection mechanisms, and empowerment of workers and trade unions to ensure that minimum wage regulations operate justly and effectively in safeguarding workers’ welfare.